Wirtschaftspolitische Implikationen der COVID-19-Pandemie im Luftverkehr - Janina Scheelhaase; David Ennen; Benjamin Frieske; Klaus Lütjens; Sven Maertens; Florian Wozny (Wirtschaftsdienst, 2021)
Der Luftverkehr ist durch die Maßnahmen gegen die COVID-19-Pandemie besonders stark betroffen. Der Verkehrsrückgang betrug 2020 zum Teil mehr als 90 %. Da die Branche von großer Bedeutung ist, sind besondere staatliche Unterstützungsmaßnahmen sinnvoll, wenn die Pandemie vorbei ist und neues Wachstum einsetzt. Dabei sollten jedoch nicht nur bestimmte Unternehmen unterstützt werden, sondern die Hilfsmaßnahmen sollten auch an bestimmte Kriterien gebunden sein. – – Global air transport passenger traffic has been particularly affected by measures to combat COVID-19. Since February 2020, both the number of global passengers and passenger flight kilometers has decreased worldwide - in Western Europe by about 80 % by the end of 2020. These developments have caused financial losses for both airlines and airports worldwide, critically threatening the existence of a large number of these companies. As the industry is of great economic importance, special government support measures could contribute to the economic recovery of the aviation industry. However, not only should certain companies be supported, but the support measures should be linked to defined and transparent criteria.
Keywords: L93; L98; G32; 330